PENGHITUNGAN RISIKO DALAM KEPUTUSAN INVESTASI PADA EMITEN SEKTOR KONSTRUKSI INDEKS KOMPAS100 DENGAN METODE CAPITAL ASSET PRICING MODEL DAN RASIO PROFITABILITY SETELAH MASA PANDEMIC COVID-19 - Sumendap, Steinly; Pontoh, Winston; Budiarso, Novi Swandari (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2021)
The risk in an investment activity is always there and it cannot be denied that these risk factors influence someone to invest. After the Covid-19 pandemic period and vaccines have been carried out so that development in Indonesia will start running again. So the CAPM (Capital Asset Pricing Model) approach in assessing a stock that is less risky to the overall market price in the Kompas100 index and the NPM (Net Profit Margin) probability ratio on stocks that are always able to generate profits every year are expected to help the public and potential investors. in making investment decisions in accordance with the risk profile.